Attachment, Social Value Orientation, Sensation Seeking, and Bullying in Early Adolescence - Innamorati, Marco; Parolin, Laura; Tagini, Angela; Santona, Alessandra; Bosco, Andrea; De Carli, Pietro; Palmisano, Giovanni L.; Pergola, Filippo; Sarracino, Diego (Frontiers in Psychology, 2018)
In this study, bullying is examined in light of the “prosocial security hypothesis”— i.e., the hypothesis that insecure attachment, with temperamental dispositions such as sensation seeking, may foster individualistic, competitive value orientations and problem behaviors. A group of 375 Italian students (53% female; Mean age = 12.58, SD = 1.08) completed anonymous questionnaires regarding attachment security, social values, sensation seeking, and bullying behaviors. Path analysis showed that attachment to mother was negatively associated with bullying of others, both directly and through the mediating role of conservative socially-oriented values, while attachment to father was directly associated with victimization. Sensation seeking predicted bullying of others and victimization both directly and through the mediating role of conservative socially-oriented values. Adolescents’ gender affected how attachment moderated the relationship between sensation seeking and problem behavior.